THE CONCEPTUAL DEFECT OF THE LAW OF UNIVERSAL GRAVITATION OR FREE FALL: A DIALECTICAL REASSESSMENT OF KEPLERS LAWS: - Malek, Abdul (JOURNAL OF ADVANCES IN PHYSICS, 2017)
The concept of Universal Gravitation or Free Fall common to both Newtons Law and the Theory of General Relativity (GR) of Albert Einstein is one-sided, idealistic and an anti-dialectical notion in cosmology. It is also in violation of the successful principle of Newtons Third Law of equal and opposite reaction and the impossibility of the existence of a single isolated force in terrestrial mechanics. This conceptual defect of the theories of gravity as universal attraction leads to superluminal velocity of free falling mass points, cosmic paradoxes, singularities, Black Holes, dark matter and other cosmic mysteries. A reassessment of Keplers laws and a dialectical approach to astrophysics in particular and to cosmology in general, is proposed.